Pengaruh Tabungan Mudharabah, Deposito Mudharabah Terhadap Pembiayaan Mudharabah Pada BPRS Di Indonesia Priode 2019-2022 - Nurul Apriani; Asyari Hasan (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine how the influence of Mudharabah Savings, Mudharabah Deposits on Mudharabah Financing at BPRS in Indonesia for the period 2019-2022. This research uses quantitative research methods. The results of the study were tested with multiple linear regression using the IBM SPSS_24 programme, while the data collection of BPRS in Indonesia for the 2019-2022 period was directly obtained after conducting research on BPRS in Indonesia for the 2019-2022 period. The sample technique in this study is to use saturated sampling or total sample, namely sampling when all populations are used as samples. Based on the t-test test that the Mudharabah Savings variable (X1) has a tcount value < ttable (10.789 < 2.201), and the Mudharabah Deposit variable (X2) has a tcount value> ttable (1.435 > 2.201), this proves that there is no effect of Mudharabah Savings (X1) on the increase in Mudharabah Financing at BPRS in Indonesia priode 2019-2022 persially while the Mudharabah Deposit variable (X2) has an influence on Mudharabah Financing at BPRS in Indonesia priode 2019-2022. And based on the results of the F-test data analysis shows that simultaneously or together the Mudharabah Savings (X1) and Mudharabah Deposit (X2) variables simultaneously affect Mudharabah Financing (Y), where the sig value is 0.158